Homozygous DMRT2 variant associates with severe rib malformations in a newborn. Issue 5 (21st April 2018) - Bouman, Arjan; Waisfisz, Quinten; Admiraal, Jop; van de Loo, Moniek; van Rijn, Rick R.; Dimitra, Micha; Oostra, Roelof‐Jan; Mathijssen, Inge B.
Abstract : Spondylocostal dysostosis (SCD) is a rare disorder characterized by vertebral segmentation defects and malformations of the ribs. SCD patients have some degree of (kypho)scoliosis, short stature and suffer from respiratory impairment due to the reduced size of their thoracic cage. Mutations in DLL3, MESP2, LFNG, HES7, TBX6, and RIPPLY2 are known to cause different subtypes of SCD. Here, we report on a male neonate with an apparent distinct SCD‐like phenotype only partly overlapping the previously described SCD subtypes. The proband presented with severe rib malformations (missing, fused, bifid, and hypoplastic ribs), vertebral malformations (intervertebral fusions of the laminae and irregular ossification of the vertebral bodies), and a mild scoliosis. Clear segmentation defects of the vertebral bodies were lacking. Other dysmorphic features were present as well. Severe respiratory insufficiency was present from birth. Whole exome sequencing identified a homozygous start‐loss variant in DMRT2 (NM_006557.6: c.1A > T p.[Met1?]) being a likely cause of the SCD‐like phenotype in the proband. Mutations in DMRT2 (OMIM#604935) have not been described in relation to SCD‐related phenotypes in humans before. However, Dmrt2 knock‐out mice exhibit severe rib and vertebral defects that strikingly overlap with the radiological phenotype of the proband reported here. Therefore, it seems plausible that mutations in DMRT2 are associated with a different (novel) subtype of SCD mainly characterized by severe rib anomalies but lacking clear segmentation defects of the vertebral bodies.